Application of IoT Based Renewable Energy For Electric Power Laboratory Campus C In Politeknik Piksi Ganesha - Muhammad Wildan Naufal Hilmi; Ardelia Astriany Rizky; Istito'a Pebrianti Pramanik; Rifki Maulana Sidik; Oscar Rachman (Politeknik Piksi Ganesha Indonesia, 2023)
The rapid advancement of technology has increased efficiency in human activities while also escalating electricity consumption, especially with the implementing of the Industry 4.0 revolution in Indonesia. To enhance the use of renewable energy, IoT technology is employed to optimize system performance with real-time data and remote control. In the second-floor laboratory of campus c Piksi Ganesha Polytechnic, there are frequent power outages due to simultaneous use of the lab. The advantage of using this energy is that PLN electrical sources can be replaced using solar panels. This research integrates renewable energy with IoT to improve laboratory electricity usage efficiency. An ESP32-based solar panel is used to collect and control energy data. Successful testing demonstrates the ability of this system, with a 67% utilization of renewable energy. The solar cell requires attention from hardware devices. The integration of renewable energy with Telegram is efficient and can be applied to another system.